Determinasi Pesan Kampanye #MYBABYTREE di Akun Instagram @wwf_id terhadap Partisipasi Followers dalam Melakukan Pelestarian Hutan - Anggi Dwi Puspita Sari; Sadakita Br Karo; Laurencia Steffanie Mega Wijaya Kurniawati; Harry; Joshua Fernando (JCommsci - Journal Of Media and Communication Science, 2022)
This paper aims to determine the extent of the influence of the #MyBabyTree campaign message on the @wwf_id Instagram account on followers' participation in replanting forests. This research method is a survey with a quantitative approach with a simple linear regression analysis technique. The results of the study show the determination of the #MyBabyTree campaign message on the @wwf_id Instagram account on the participation of followers to replant forests by 43.4%, while 56.6% is influenced by other variables from outside this study. In conveying the #MyBabyTree message, you should pay attention to the order of presentation message structure, namely by conveying a strong argument at the beginning of the sentence, such as: writing a caption regarding the sentence asking to plant a tree is placed at the beginning because people pay more attention to the first message in a series of messages. Information on the lack of mangrove forest cover must include an explanation in the form of education for the community, such as: providing education about the contribution of mangrove forests in the bulwark of abrasion prevention and how to maintain and preserve mangrove forests. Supported by the theory used S-O-R (Stimulus, Organism, Response) this can be one of the contents of messages based on emotional appeals, namely messages that evoke positive emotions that provide encouragement to followers. The Instagram account @wwf_id in conveying the #MybabyTree message should use words or sentences that are clear, concise, firm, lively, real, easy to remember, ethical, and aesthetic, such as: "Mangrove cover" is changed to "The area of ​​mangrove forest".